Stress perception among patients in pre-colonoscopy period and those undergoing chemotherapy treatment - Silva, Graziela de Souza Alves da; Silva, Gabriela Alves Vieira da; Antonietti, Camila Cristine; Benavente, Sonia Betzabeth Ticona; Silva, Rodrigo Marques da; Costa, Ana Lucia Siqueira (Rev Rene, 2015)
Objective: comparing the perception of stress among patients with colorectal cancer undergoing chemotherapy with those in pre-colonoscopy period. Methods: a comparative descriptive study developed with 144 people receiving chemotherapy and 100 patients in the pre-colonoscopy period, using biosocial and clinical data, Stress Assessment Tool and Perceived Stress Scale. Results: a predominance of females (73%), aged over 65 (50%) were predominant for the pre-colonoscopy period patients. In patients receiving chemotherapy, gender parity with ages ranging from 40-64 years (68.1%) was observed. Precolonoscopy patients showed higher perceived stress compared to those receiving chemotherapy (p <0.001). Conclusion: the phase of diagnostic definition represents greater stress to patients in comparison to period of treatment, even despite the characteristic manifestations of chemotherapy.